2005
DOI: 10.1248/bpb.28.101
|View full text |Cite
|
Sign up to set email alerts
|

19.ALPHA.-Hydroxyursane-Type Triterpenoids: Antinociceptive Anti-inflammatory Principles of the Roots of Rosa rugosa

Abstract: The roots of Rosa rugosa (Rosaceae) have traditionally been used to treat diabetes mellitus, pain, and chronic inflammatory disease in Korea.1) Previously, the hypoglycemic principle, catechin, 2) was isolated together with triterpenoids, along with the 28-glucosides of euscaphic acid, tormentic acid, and arjunic acid from this crude drug. 2,3) We have previously reported on triterpenoids with antinociceptive/antiinflammatory action, e.g., oleanolic acid, momordin Ic, 4) hederagenin, kalopanaxsaponin A, 5) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 12 publications
1
35
0
2
Order By: Relevance
“…Our results are in agreement with other numerous studies which demonstrated that polyphenols-rich extracts could inhibit the NO production in LPS-stimulated macrophages [49][50][51].…”
Section: Anti-inflammatory Effect Of Methanolic Extract Of Leaves Of supporting
confidence: 94%
“…Our results are in agreement with other numerous studies which demonstrated that polyphenols-rich extracts could inhibit the NO production in LPS-stimulated macrophages [49][50][51].…”
Section: Anti-inflammatory Effect Of Methanolic Extract Of Leaves Of supporting
confidence: 94%
“…1) used for this study were isolated from the roots of R. rugosa as previously described [13]. These isolated compounds were determined by LC-MS and found to be 95% pure.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that TA has potent anti-inflammatory effects against TPA-and carrageenan-induced inflammation [13]. However, the molecular targets and the molecular mechanisms underlying the anti-inflammatory activities of TA are poorly understood.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Previous research has revealed the presence of many biologically active compounds in all parts of R. rugosa [1,[4][5][6][7]. Many of them act as potential natural antioxidants [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…common cold [3]. Despite the great commercial potential of the R. rugosa, only a few reports have been published about the phytochemical content and biological activity of this plant; in particular, the knowledge of its roots and leaves remains limited, which is surprising considering that rose roots have been utilized by Asian folk medicine to treat conditions such as diabetes mellitus, pain and chronic inflammatory diseases [4].Previous research has revealed the presence of many biologically active compounds in all parts of R. rugosa [1,[4][5][6][7]. Many of them act as potential natural antioxidants [8][9][10].…”
mentioning
confidence: 99%